Evolution, Taxonomy, and Terminology of Rasmi [electronic resource] - Reza Hashemi Nik; Ahmad Iskandar Syed Ariffin (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2008